A young traveller's journal of a tour : in North and South America during the year 1850 - Welby, Victoria, Lady, 1837-1912 (Preservation and Access for American and British Children's Literature, 1850-1869 (NEH PA-23536-00), 1852)
Journal entries tracing the travels of a 12-year-old girl through the continent of America.